The Effectiveness of Wayground as a Gamified Assessment Tool for Mastering Vocabulary at a Junior High School - Devi Septiana; Umar Alfaruq A. Hasyim; Wiwied Pratiwi; Rizky Hidayatullah (Prodi Tadris Bahasa Inggris, 2026)
The present study employed a quasi-experimental design involving seventh-grade students from classes VII A and VII B at SMP Negeri 02 Abung Surakarta. Vocabulary mastery was emphasized as a core element of English language learning, as it serves as the foundation for developing key language skills, including reading, writing, and speaking. In this study, Wayground was employed as a gamified assessment tool in class VII A, whereas class VII B received instruction and assessment through conventional methods. The post-test results showed that students in class VII A obtained a higher mean score (89.05) compared to those in class VII B, who achieved a mean of 72.78. To examine the significance of this difference, an independent samples t-test assuming unequal variances (Welch’s t-test) was performed at the 0.05 significance level. The analysis revealed a t-value of 2.84, which was greater than the critical value of 2.06, and the p-value (0.008) was lower than 0.05, confirming statistical significance. Therefore, the null hypothesis (H₀) was rejected. These findings indicate that Wayground is more effective than conventional assessment methods and supports the integration of gamified digital assessment to enhance students’ vocabulary mastery.